Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1210/jc.2011-1576
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Gluteal Expression of Adipogenic and Lipogenic Genes in Black South African Women Is Associated with Obesity-Related Insulin Resistance

Abstract: Context Black South African women are less insulin sensitive than their white counterparts, despite less central and greater peripheral fat deposition. We hypothesized that this paradox may be explained, in part, by differences in the adipogenic capacity of subcutaneous adipose tissue (SAT). Objective To measure adipogenic and lipogenic gene expression in abdominal and gluteal SAT depots, and determine their relationships with insulin sensitivity (SI) in South African women. Design Cross-sectional. Parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 20 publications
3
30
1
Order By: Relevance
“…Related to the increased presence of small adipocytes, the expression of genes related to adipogenesis was also lower in insulin-resistant individuals (McLaughlin et al, 2007). These findings are consistent with independent reports of reduced adipogenesis in insulinresistant patients (Goedecke et al, 2011;Yang et al, 2004). Furthermore, these expression changes were also associated with modest increases in inflammatory activity in insulin-resistant AT (McLaughlin et al, 2008).…”
Section: Regional Variation In Adipose Morphologysupporting
confidence: 87%
“…Related to the increased presence of small adipocytes, the expression of genes related to adipogenesis was also lower in insulin-resistant individuals (McLaughlin et al, 2007). These findings are consistent with independent reports of reduced adipogenesis in insulinresistant patients (Goedecke et al, 2011;Yang et al, 2004). Furthermore, these expression changes were also associated with modest increases in inflammatory activity in insulin-resistant AT (McLaughlin et al, 2008).…”
Section: Regional Variation In Adipose Morphologysupporting
confidence: 87%
“…However, when the capacity to store excess fat in the periphery is exceeded, peripheral fat is no longer protective. A small SA study demonstrated reduced adipogenesis and lipogenesis in obese black women, and this was associated with increased IR 18. Furthermore, a recent study from our laboratory has shown that with increasing weight gain, black women accumulated more central relative to peripheral FM, which was associated with the development of IR 35.…”
Section: Discussionmentioning
confidence: 87%
“…Yet, many studies in South Africa and the USA have shown that at the same level of BMI or waist circumference, black women are more insulin resistant than their white counterparts, despite having less VAT [46]. The major contributor to abdominal fat in African women is SAT, largely superficial rather than deep SAT [12, 13], and is accompanied by greater peripheral (gluteo-femoral) fat [14]. Thus, irrespective of the size of the depot, there is evidence of ethnic differences in the association between regional fat distribution and insulin sensitivity.…”
Section: Body Fat Distributionmentioning
confidence: 99%
“…In black South African women, this association is stronger for the deep SAT than the superficial SAT depot [12]. Further, we showed for the first time that gluteal SAT is negatively correlated with insulin sensitivity in black, but not white women [14]. …”
Section: Body Fat Distributionmentioning
confidence: 99%